EVALUATING THE EFFECTS OF a COEFFICIENT IN GREY THEORY TO FORECASTING ACCURACY AND BULLWHIP EFFECT - Tasdemir, Funda Ahmetoglu; Gulsun, Bahadir (YILDIZ TECHNICAL UNIV, 2013)
The initial step of production system is demand forecasting which is significant for protecting stock levels, providing better customer service, improving capacity usage and increasing profits. To realize all these organizational objects, it is essential to increase forecasting accuracy. Beside this, one another issue should be taken into consideration to reach these goals, which takes place as bullwhip effect in literature. Bullwhip effect is directly influenced by forecasting method used. Despite there are so many studies about increasing forecasting accuracy in literature, there is not much which refers to increasing accuracy of the forecasting method and the bullwhip effect the method causes together. In this study we investigated a coefficient in grey theory from both perspectives. The study is supported with real-data of 12 months showing positive trend which is taken from an electric company in Turkey.
Keywords: Demand forecasting; forecasting accuracy; bullwhip effect; grey theory; Engineering